Monopoly prices versus Ramsey-Boiteux prices: are they similar, and: does it matter? - Felix Höffler (Max Planck Institute for Research on Collective Goods, 2004)
Ramsey-Boiteux prices and monopoly prices are frequently regarded as being similar. This might suggest that, in particular in network in- dustries with large xed costs, sometimes monopoly pricing is close to the Ramsey-Boiteux second best and welfare superior to imperfectly regulated prices. This paper tries to specify what is meant by being similar, and it analyzes the welfare implications that can be drawn from comparing both sets of prices. Interdependence of demand and the impact of competition are discussed. We reinforce the view that monopoly prices are usually not similar, and even if they are, this implies no positive welfare judgments on monopoly pricing.
Keywords: L33; L50; L94; 330; Ramsey Pricing; Regulation; Access Pricing; Termination; Ramsey-Preis; Monopol; Netzzugang; Theorie